MATERNAL AND FETAL OUTCOMES IN HYPOTHYROID PREGNANT WOMEN: INSIGHTS FROM A HOSPITAL-BASED STUDY IN MANDI, HIMACHAL PRADESH - DONKA, BHARGAVI; MAHAJAN, HEMENDER; SHARMA, NALNEESH (International Journal of Current Pharmaceutical Research, 2023)
Objective: Thyroid disorders significantly impact maternal and fetal health during pregnancy, with thyroid hormone balance being crucial for fetal development. Hypothyroidism, a common disorder among women of childbearing age, can lead to adverse pregnancy outcomes, including subtle thyroid dysfunction and autoimmune conditions. Diagnosing thyroid disorders in pregnancy is challenging due to overlapping symptoms with normal pregnancy changes and various contributing factors. Methods: In this prospective observational study conducted in Mandi, Himachal Pradesh, we focused on pregnant women attending the first-trimester antenatal clinic. Inclusion criteria comprised pregnant women aged 18 or older, regardless of their gravidity and parity, who provided informed consent. Exclusions were made for comorbidities such as diabetes, hypertension, renal or liver disease, multifetal gestation, and previous bad obstetric history. A total of 300 hypothyroid pregnant women were selected through convenience sampling. We assessed serum thyroid-stimulating hormone (TSH) levels using chemiluminescent microplate immunoassay (CMIA) and administered adequate L thyroxine treatment to maintain TSH levels below 2.5 mIU/l. Results: Maternal outcomes exhibited variation, with common delivery methods being cesarean sections (both emergency and elective) and normal vaginal deliveries. Some pregnancies faced complications, including gestational diabetes mellitus, preterm birth, and placenta previa. Neonatal outcomes ranged from healthy newborns to those with low Apgar scores, intrauterine demise, low birth weight, and stillbirth. Adequate treatment with L thyroxine was observed in 60.6% of cases, emphasizing the need for improved hypothyroidism management during pregnancy. Conclusion: Our study underscores the diversity of maternal and neonatal outcomes associated with hypothyroidism during pregnancy in a hilly region of India. Early detection, comprehensive antenatal care, and optimal thyroid hormone management are vital to minimize complications and promote the well-being of both mothers and newborns. Further research and awareness campaigns are essential for enhancing thyroid disorder screening and management in pregnancy.